HUBUNGAN PENERAPAN BUDAYA 5S (SENYUM, SAPA, SALAM, SOPAN, SANTUN) TERHADAP KEPUASAN PELANGGAN DI APOTEK MARFA CIANJUR: The Relationship between the Implementation of 5S Culture (Smile, Greet, Say Hello, Be Polite, Courteous) and Customer Satisfaction at Pharmacy X - Wulan Nur Azhar; Dian Fitri Chairunnisa; Leli Nurlaeli (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2026)
Pharmaceutical services in community pharmacies should not only focus on technical accuracy, but also on the quality of interpersonal interaction between pharmaceutical personnel and customers. The 5S culture (smile, greet, salutation, politeness, and courtesy) is one service approach that may support customer satisfaction. This study aimed to analyze the relationship between the implementation of 5S culture and customer satisfaction at Marfa Pharmacy, Cianjur. This research used a quantitative, non-experimental, cross-sectional design. The sample consisted of 347 customers selected using accidental sampling. Data were collected using Likert-scale questionnaires measuring 5S culture and customer satisfaction based on SERVQUAL dimensions. Data were analyzed using univariate analysis and Spearman rank correlation. Most respondents were female (68.0%), aged 26-35 years (40.1%), had visited the pharmacy 2-5 times (47.0%), and came mainly to buy over-the-counter medicines (42.9%). The implementation of 5S culture was generally in the moderate-to-good category, while customer satisfaction was in the moderate category. Spearman correlation showed a positive and significant relationship between 5S culture and customer satisfaction (rho = 0.501; p = 0.000). The better the implementation of 5S culture, the higher the level of customer satisfaction.